THE EFFECT OF COMMUNITY CHARACTERISTICS ON ACHIEVEMENT OF SANITATION ACCESS POLICY DEVELOPMENT IN MALUKU PROVINCE - Tehupeiory, Aarce; Sari, Mega Mutiara; Sianipar, Imelda Masni Juniaty; Suryawan, I Wayan Koko; Septiariva, Iva Yenis (Department of Urban and Regional Planning, Universitas Diponegoro, 2023)
Maluku Province is an area with minimal access to sanitation because of its archipelagic location. Access to sanitation is one indicator of sustainable development goals (SDGs) that must archive in 2030. To achieve sustainable universal sanitation access, an indicator is needed that can be used to make policies that can grow access to proper sanitation. This study aims to determine the factors that can improve sanitation in Maluku Province. The development of livable housing must also pay attention to access and proper sanitation. This study used secondary data to analyze multilinear regression of socioeconomic impact on access to sanitation. Economic growth affects people's welfare. Economic growth is usually followed by a reduction in poverty, an increase in the Human Development Index (HDI), and an expansion of employment opportunities. This study uses secondary data from 2006 to 2016. Integrating human development, reducing poverty, and increasing residential ownership is needed to increase Maluku Province's sanitation access. With improved policies and better master plans for improving the quality of social variables, this variable will also affect increasing access to sanitation in Maluku Province. Better policy and programs from the central and local governments should seek to reduce poverty levels to improve access to sanitation in Maluku Province.